2018
DOI: 10.2166/wst.2018.183
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the reduction of antibiotic-sensitive and antibiotic-resistant Escherichia coli as a result of low- and medium-pressure UV lamps

Abstract: It is vital that harmful bacteria are removed from water and wastewater treatment plants to prevent human/environmental exposure. This paper examines the log reduction of antibiotic-sensitive (AS) and antibiotic-resistant (AR) Escherichia coli (E. coli) as a result of low-pressure (LP) and medium-pressure (MP) UV lamps. A meta-analysis was performed and a mixed-effect model was created in which 303 data points on the log reduction of E. coli from UV treatment were collected. The results show that in order to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…For low-pressure lamps, 8.1 mJ/cm 2 UV was required for antibiotic sensitive E. coli and 8.4 mJ/cm 2 UV for antibiotic resistant E. coli. The study confirmed there was no statistical difference between the inactivation of antibiotic sensitive and resistant E. coli by UV and supports the idea that the behavior of ARB may be similar to antibiotic susceptible bacteria (O'Flaherty, Membr e, & Cummins, 2018).…”
Section: Challenging Questions Regarding the Arb And Args In Aquatic Environmentssupporting
confidence: 79%
“…For low-pressure lamps, 8.1 mJ/cm 2 UV was required for antibiotic sensitive E. coli and 8.4 mJ/cm 2 UV for antibiotic resistant E. coli. The study confirmed there was no statistical difference between the inactivation of antibiotic sensitive and resistant E. coli by UV and supports the idea that the behavior of ARB may be similar to antibiotic susceptible bacteria (O'Flaherty, Membr e, & Cummins, 2018).…”
Section: Challenging Questions Regarding the Arb And Args In Aquatic Environmentssupporting
confidence: 79%
“…Several causes are involved in the appearance of drugs in environmental matrices. Overuse, misuse and incomplete therapeutic treatments are the main factors generally related to this increase (O'Flaherty et al 2017). Another can be eliminated via excretion, in the unmodified form (original drug) and as metabolites, which can be converted into other transformation products, both by metabolism and by degradation processes (Kümmerer et al 2016;Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate the inactivation of enteric bacteria, viruses, bacterial spores, and protozoan cysts and oocysts as an effective technique for disinfecting wastewater, especially for water reuse and recovery (Oliveira et al 2008 ; Liang et al 2013 ; O´Flaherty et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%